Pembuktian Tindak Pidana Zina Berdasarkan Bukti Petunjuk: Analisis Putusan Pengadilan No. 506/Pid.B/2017/PN Smn - Dayu Putra (Universitas Islam Indonesia, 2020)
This study discusses the use of indicative evidence as a basis for proving adultery and what kind of indicative evidence has the justification for proving adultery. The research method used is normative juridical with a case and statutory approach. The results of the study concluded that: First, the use of indicative evidence is very much dominated by the subjectivity of judges. This evidence is used after the judge is absolutely sure that the defendant has committed adultery based on the conformity and logical relationship between each fact and the element of adultery that is to be proven. When using indicative evidence, the judge strongly emphasized the fact that the defendant was together in a closed room within a period of time that allowed for adultery, to be linked to the Supreme Court Decision Number 854K / Pid / 1983, which became the legal source of proof of adultery or sexual intercourse. The use of indicative evidence is always linked to the inability of the defendant to prove his argument; and Second, indicative evidence that has justification must meet the formal and material requirements.